2004
DOI: 10.1007/s00335-003-2286-8
|View full text |Cite
|
Sign up to set email alerts
|

Genotype of stearoyl-CoA desaturase is associated with fatty acid composition in Japanese Black cattle

Abstract: To investigate the genetic factors that affect fatty acid composition of beef, we compared the full-length bovine stearoyl-CoA desaturase (SCD) cDNA from 20 Japanese Black steers. Two types of the SCD gene with single nucleotide polymorphisms (SNPs) were observed in the ORF of SCD cDNA, in which an amino acid replacement from valine (type V) to alanine (type A) was predicted. We developed a method for genotyping these two SCD genes based on PCR-RFLP. We have classified 1003 Japanese Black carcasses into three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
226
3
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(261 citation statements)
references
References 23 publications
23
226
3
9
Order By: Relevance
“…Similar to previous reports (Asadollahpour Nanaei et al, 2013), the frequencies for the A and V alleles of the SCD1-A293V polymorphism in the current study were 0.58 and 0.42, respectively. Consistent with results from the present study, a higher frequency of the A allele in comparison with the V allele has been reported in Japanese Black cattle (Taniguchi et al, 2004), Italian Holstein (Mele et al, 2007), Valdostana breed (Moioli et al, 2007) and Canadian Jersey (Kgwatalala et al, 2009). On the contrary, in the Piedmontese breed (Moioli et al, 2007) and Italian Brown cattle (Conte et al, 2010) the V allele had a higher frequency compared with the A allele.…”
Section: Resultssupporting
confidence: 92%
“…Similar to previous reports (Asadollahpour Nanaei et al, 2013), the frequencies for the A and V alleles of the SCD1-A293V polymorphism in the current study were 0.58 and 0.42, respectively. Consistent with results from the present study, a higher frequency of the A allele in comparison with the V allele has been reported in Japanese Black cattle (Taniguchi et al, 2004), Italian Holstein (Mele et al, 2007), Valdostana breed (Moioli et al, 2007) and Canadian Jersey (Kgwatalala et al, 2009). On the contrary, in the Piedmontese breed (Moioli et al, 2007) and Italian Brown cattle (Conte et al, 2010) the V allele had a higher frequency compared with the A allele.…”
Section: Resultssupporting
confidence: 92%
“…The SCD gene is associated with fatty acid composition and converts stearic acid into oleic acid. Recently, Taniguch et al (7) reported that a non-synonymous SNP in Exon IV of the SCD gene lead to a change in the monounsaturated fatty acid composition in Japanese black cattle. In addition, the SCD enzyme activity was positively correlated with unsaturated fatty acid composition (8).…”
Section: Resultsmentioning
confidence: 99%
“…RA may also originate from endogenous synthesis by way of the stearoyl Co-A desaturase (SCD) enzyme, which is able to insert a double bound in the cis-9 position in a large spectrum of fatty acids, including VA. The level of the SCD expression was tested in lactating and growing cattle (Delbecchi et al, 2001and Taniguchi et al, 2004, but little is known about the SCD activity in pre-weaning lambs. SCD activity may be determined by tissue sampling, but this method is very expensive and invasive.…”
Section: Discussionmentioning
confidence: 99%